Tingkat Pemahaman Kognitif Peserta Didik dalam Bermain Basket Pasca Daring di Sekolah - Muhammad Sulthan Zaka; Muhammad Mury Syafei; Rustam Effendi (Journal on Education, 2023)
This study aims to determine the level of cognitive understanding of students in playing basketball after daring (post-online) at school. This type of research is descriptive quantitative with survey research methods. The research subjects totaled 100 students of SMAN 1 at Cigombong, from the results of determining the purposive sampling technique. The instrument used was a questionnaire with a Likert scale of 5. Based on the results of the research, the following data were obtained: 1. Results based on the stages of prior knowledge, the highest frequency was in the 'good' category of 53.00% or 53 students. Meanwhile, in the 'very good' category 0% or 0 students, in the 'fair' category 21% or 21 students, in the 'less' category 19% or 19 students, and in the 'very good' category less' by 7% or 7 students. 2. The results are based on the stages of implementation knowledge, the highest frequency shows in the 'sufficient' category of 50.00% or 50 students. Meanwhile, in the 'very good' category 9% or 9 students, in the 'good' category 15% or 15 students, in the 'less' category 24% or 24 students, and in the 'very good' category less' by 2% or 2 students. 3. Based on the results of the final knowledge stage, the highest frequency is in the 'sufficient' category of 59.00% or 59 students. Meanwhile, in the 'very good' category 10% or 10 students, in the 'good' category 13% or 13 students, in the 'less' category 12% or 12 students, and in the 'very good' category less' by 6% or 6 students. 4. Based on the results of the overall stages, the highest frequency is in the 'enough' category of 53.00% or 53 students. Meanwhile, in the 'very good' category 9% or 9 students, in the 'good' category 13% or 13 students, in the 'less' category 20% or 20 students, and in the 'very good' category less' by 5% or 5 students.